MANAGEMENT OF EDUCATOR AND EDUCATION STAFF HUMAN RESOURCES IN SMK BINA SEJAHTERA 4 VOCATIONAL SCHOOL BOGOR - Muhammad Hidayat Ginanjar; Rahman Rahman; Muhamad Syukur (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to determine the management of human resources, especially educators and education staff in vocational high schools. The object of this research is SMK Bina Sejahtera 4 Bogor City. The focus of this research is laid out into several sub-focus research problems such as; (1) The system for recruiting human resources for teachers and education personnel, (2) The system for developing and enhancing the competence of human resources for educators and educational personnel, (3) Barriers and solutions for HR development. This research method uses qualitative methods with data collection through observation, interviews, and documentation study. The main informant of this research is the principal, and the supporting informants are teachers and staff. The data analysis technique used by the author is triangulation which includes triangulation of data, methods, and sources. The research results include; (1) The recruitment system for teachers and education staff is already running well, (2) The HR development system for teachers and education staff is quite good and by their professionalism, (3) There are still a few obstacles in developing HR competencies, especially the limited cost of education. As an alternative solution made by the principal of SMK Bina Sejahtera 4 is involving teachers in various training activities such as; subject teacher deliberation (MGMP), principal work deliberation (MKK), and training activities organized by the Bogor City Education Office.